Ocurrence of Staphylococcus aureus and multiplex pcr detection of classic enterotoxin genes in cheese and meat products - Pelisser, Marcia Regina (Sociedade Brasileira de Microbiologia, 2009)
Multiplex PCR was used to investigate the presence of enterotoxins genes (sea, seb, sec, sed and see) and femA gene (specific for Staphylococcus aureus) in coagulase-positive staphylococci (CPS) isolated from cheese and meat products. From 102 CPS isolates, 91 were positive for femA, 10 for sea, 12 for sed and four for see.